Detection of viral hemorrhagic septicemia virus by quantitative reverse transcription polymerase chain reaction from two fish species at two sites in Lake Superior - Cornwell, Emily R (Journal of aquatic animal health, 2011)
Viral hemorrhagic septicemia virus (VHSV) was first detected in the Laurentian Great Lakes in 2005 during a mortality event in the Bay of Quinte, Lake Ontario. Subsequent analysis of archived samples determined that the first known isolation of VHSV in the Laurentian Great Lakes was from a muskellunge Esox masquinongy collected in Lake St. Clair in 2003. By the end of 2008, mortality events and viral isolations had occurred in all of the Laurentian Great Lakes except Lake Superior. In 2009, a focused disease surveillance program was designed to determine whether VHSV was also present in Lake Superior. In this survey, 874 fish from 7 sites along the U.S. shoreline of Lake Superior were collected during June 2009. Collections were focused on nearshore species known to be susceptible to VHSV. All fish were dissected individually by using aseptic techniques and were tested for the presence of VHSV genetic material by use of a quantitative reverse transcription (qRT) polymerase chain reaction (PCR) targeting the viral nucleoprotein gene. Seventeen fish from two host species at two different sites tested positive at low levels for VHSV. All attempts to isolate virus in cell culture were unsuccessful. However, the presence of viral RNA was confirmed independently in five fish by using a nested PCR that targeted the glycoprotein (G) gene. Partial G gene sequences obtained from three fish were identical to the corresponding sequence from the original 2003 VHSV isolate (MI03) from muskellunge. These detections represent the earliest evidence for the presence of VHSV in Lake Superior and illustrate the utility of the highly sensitive qRT-PCR assay for disease surveillance in aquatic animals